Makna Kekerasan Dalam Pacaran Pada Pria - Yunika Zhaffirah; Eva Meizara Puspita Dewi; Muh. Nur Hidayat Nurdin (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
Violence in courtship occurs in a relationship that is not merely done by men against women. It turns out that men can also experience violence committed by women in a dating relationship. This study aims to determine the meaning of violence in dating in men. This study uses a qualitative method with a phenomenological approach. Respondents numbered 3 people aged 24 years and 27 years. Research data collection techniques using unstructured interviews. The results of data analysis show that individuals get acts of violence in courtship, conflict occurs due to misunderstanding and possessive attitudes of the couple, as well as at the time of the incident of the perpetrators and victims did not care about the surrounding environment. The implications of research results prove that men also often get violent behavior by couples. Violence in courtship can cause psychological and physical impacts for individuals. This negative impact makes the victim feel traumatized, shame, hurt, afraid and not good for mental health. The physical impact makes the victim have bruises due to blows from the perpetrators and bleeding on the face and neck area. The individual assesses that the ideal partner does not demand too much to a partner, requires mutual trust and maintaining feelings for each other.